Minimizing the Use of Restraint in Patients with Mental Disorders at a Mental Hospital: A Systematic Review - Achmad Syamsudin; Fakhrun Nisa Fiddaroini; Maulidiyah Junnatul Azizah Heru (Jurnal Ners, 2019)
Background: Restraint in the psychiatric unit is a common practice but it is very controversial and it has undergone a poor evaluation according to methodological investigations. Using restraint is a common problem and has a significant impact on patients, families and health care staff. Therefore, this systematic review will discuss the important reasons as to why restraint should be reduced. It will also explain several alternative treatments for aggressive patients in mental hospitals.Method: The database searches were used to identify potential articles: Scopus and Proquest were the focus. The search was limited to those published in the range of the last 5 years from 2013 to 2018. The keywords that were used were ‘restraint in the hospital’, ‘restraint reduction’, ‘the elimination of restraint’ and ‘physical restraint’.Result: Only 15 articles met the inclusion criteria. The results suggest that restraint is considered to be a violation of human rights and that it traumatizes the patients. It is inhuman and degrading. Besides this, restraint can result in physical complications in the form of lacerations, asphyxia, thrombosis and death. Restraint is permitted when other methods fail and in emergency conditions.Conclusion: Some of the ways to reduce the use of restraint are by constant monitoring and through the control of individual behavior, including verbal management and attitudes, reducing the environmental risks, and administering drugs. Some of the efforts to avoid restraint are the "Positive and Safe in Calderstones" program, sensory modulation and peer advice and support.